Pat Perry - Sahl, Ted (photographer):::Creator::::::::::::
Photograph shows Pat Perry. Perry was a pioneer activist with San Jose's Lambda Association and is wearing a button with the Lambda symbol on it. Partially visible is an arm around Perry's shoulders with their hand resting on Perry's left shoulder.